AB0663 EFFICACY OF BIOLOGICAL THERAPY IN TREATMENT OF ANKYLOSING SPONDYLITIS IN SERBIA. (2nd June 2020) - Zivanovic Radnic, T.; Cvetkovic, J.; Erdeljan, B.; Veselinovic, M.; Milic, B.; Sefik Bukilica, M.; Damjanov, N.; Vojinovic, J.
Abstract : Background: Patients with ankylosing spondylitis (AS) are treated in accordance with the 2016 ASAS / EULAR recommendations. Objectives: Determine our experience and results in the treatment of AS by analysing data from the URES database collected from reference centers for the treatment of rheumatic diseases in Serbia. Methods: Retrospective insight into the database of patients treated with biological therapy in reference centers (Institute of Rheumatology in Belgrade, Institute "Niska Banja", Special Hospital Novi Sad, KC Vojvodina and KC Kragujevac) from 2009-2018. Disease activity was monitored by the BASDAI, BASFI and ASDAScrp indexes. Results: Of the 250 patients, 185 were male. The mean age at diagnosis was 33.02 ± 11.17 years. The mean length of treatment prior to initiation of biological therapy was 6.55 ± 7.82 years. There was a statistically significantly shorter duration of illness before the introduction of biological therapy in those who subsequently remained on the first drug (5.91 ± 7.53 vs 8.48 ± 8.48 years p = 0.046, p <0.05). The mean age at TNF alpha inhibitor administration was 39.61 ± 11.33 years. Patients who remained on the first drug were significantly younger when starting treatment with TNF inhibitors compared with patients who changed the first drug (38.75 ± 11.29 vs 42.46 ± 11.11 years p = 0.029, p <0.05). Those who changed the first drug were statistically longer treated with biological drugs (36.9 ± 30.03 vs 56.33 ± 32.4 months p = 0.0001). There were more patients with dactylitis and HLAB27 + in the group remaining on the first drug (p <0.05) and more with inflammatory bowel disease in the group who had the change in drug (p <0.05). The duration of etanercept therapy as the first drug was 49.11 ± 36.37 months, with the second drug 24.26 ± 27.08, and with the third drug 43 ± 45.2. Treatment with adalimumab as the first drug lasted for 28.34 ± 21.28, for the second drug 21.65 ± 14.57, for the third 3.5 months. Golimumab therapy as the first drug lasted 25.85 ± 14.58, with the second drug 20.33 ± 19.13, and as the third drug for 24 months. Therapy with infliximab as the first drug lasted 28.36 ± 23.52, with the second drug 20.3 ± 20.09, and with the third 16.5 months. According to the ASDAScrp index, 185 patients had very high disease activity (VHDA) before the first drug, high activity (HDA) 63, moderate activity (MDA) 2. At the time of the intersection, 8 had VHDA, HDA 48, MDA 106, and there were 88 patients in remission. There are 8 patients in the VHDA group who started treatment with the current drug less than 6 months ago. There are 48 patients in the HDA, of whom 17 who started treatment with the current drug less than 6 months ago, one at the time of the intersection had a urinary tract infection and high CRP, and the remaining 30 were patients with no significant decrease in ASDAS index (16 on first drug, 12 on the second drug and 2 patients on the third drug). Conclusion: In patients with AS who do not have a good response to the first anti TNFα drug, a good option to continue their treatment is to switch to the second and third drugs of the same mechanism of action (anti TNFα drug). KEY WORDS: ankylosing spondylitis, TNFα inhibitors, efficacy Disclosure of Interests: Tatjana Zivanovic Radnic: None declared, Jovana Cvetkovic: None declared, Biljana Erdeljan: None declared, Mirjana Veselinovic: None declared, Biljana Milic: None declared, Mirjana Sefik Bukilica: None declared, Nemanja Damjanov Grant/research support from: from AbbVie, Pfizer, and Roche, Consultant of: AbbVie, Gedeon Richter, Merck, Novartis, Pfizer, and Roche, Speakers bureau: AbbVie, Gedeon Richter, Merck, Novartis, Pfizer, and Roche, Jelena Vojinovic Consultant of: Roche, Abbvie, Pfizer, MSD, Speakers bureau: Roche, Abbvie, Pfizer, MSD